Optical networks conductivity computing - XU Jie (Tongxin xuebao)
The article has calculated the probability of existing wavelength paths which connect source and target in optical switch networks. It first calculated the probability of existing wavelength paths in single route without WC（wavelength converter）, second calculated small network without WC, third it calculated optical networks which include some WCs, and last it discussed some facts in wavelength switching.